Rubidium and sodium permeability of the ATP-sensitive K+ channel in single rat pancreatic beta-cells. - Ashcroft, F; Kakei, M; Kelly, R (1989)
1. The patch-clamp method has been used to study the selectivity of single ATP-sensitive potassium channels in excised membrane patches from dissociated rat pancreatic beta-cells. 2. In symmetrical K+ concentrations the current-voltage relation of this channel showed slight inward rectification. The K+ permeability coefficient was 1.05 x 10(-13) cm3/s ([K+]o = 140 mM; 20 degrees C) in the inside-out patch and somewhat smaller when measured under the same conditions in the outside-out configuration (0.86 x 10(-13) cm3/s). 3. When intracellular Rb+ replaced K+, inward K+ currents were unaffected but the outward currents carried by Rb+ were substantially smaller. The extent of the reduction in the outward currents depended on the internal Rb+/K+ ratio and increased as [Rb+]i was raised. Both inward and outward Rb+ currents were blocked by 1 mM-ATP. No currents were measurable in symmetrical 140 mM-Rb+ solutions. 4. With 140 mM [K+]o and 140 mM [Rb+]i the single-channel current-voltage relation reversed at +8 mV and the potential at which the variance of the ATP-sensitive current was least was shifted by 6 mV to more positive potentials. These data suggest a PRb/PK ratio of around 0.7. 5. Outward Rb+ currents were reduced at all potentials in inside-out patches exposed to 107 mM-Rb+ solution intracellularly and 5 mM-K+ externally. 6. Partial replacement of external K+ with Rb+ substantially reduced the inward currents recorded from outside-out patches and also decreased outward K+ currents. 7. In outside-out patches, the addition of 1 mM-Rb+ to the external solution produced a block of inward K+ currents that initially increased and then decreased again with hyperpolarization. This suggests that the Rb+ block of K+ currents is voltage dependent and that Rb+ acts as a permeant blocker of K+ currents. 8. The sodium permeability of the channel, relative to that of potassium, was 0.39 for internal Na+ and 0.007 for external Na+ ions. 9. We conclude that Rb+ serves as an acceptable tracer for K+ in efflux studies when changes in K+ flux through ATP-sensitive K+ channels are of interest but that the magnitude of such fluxes will be considerably underestimated.